KORUPSI DAN UPAYA PEMBERANTASANNYA - WIDIASTUTI, TRI WAHYU (Universitas Slamet Riyadi, 2009)
Abstract: Corruption as a crime has destroyed the life of a nation as well as paralyzed its funtion to serve, to give welfare and education to its people. It is practiced widely and systematically, involving every single state apparatus n groups. In this condition, even a good one will be segregated by others. State apparaturs does not work for the sake of people, instead they work for their own wealth. Therefore, corruption is regarded as an extra ordinary crime and its eradication effort must be in extra ordinary one as well. Keywords: corruption, extra ordinary crime.